Spinal Sensorimotor Circuits Play a Prominent Role in Hindlimb Locomotor Recovery after Staggered Thoracic Lateral Hemisections but Cannot Restore Posture and Interlimb Coordination during Quadrupedal Locomotion in Adult Cats - Johannie Audet; Sirine Yassine; Charly G. Lecomte; Stephen Mari; Félix Soucy; Caroline Morency; Angèle N. Merlet; Jonathan Harnie; Claudie Beaulieu; Louis Gendron; Ilya A. Rybak; Boris I. Prilutsky; et al. (2023)
Spinal sensorimotor circuits interact with supraspinal and peripheral inputs to generate quadrupedal locomotion. Ascending and descending spinal pathways ensure coordination between the forelimbs and hindlimbs. Spinal cord injury (SCI) disrupts these pathways. To investigate the control of interlimb coordination and hindlimb locomotor recovery, we performed two lateral thoracic hemisections on opposite sides of the cord (right T5-T6 and left T10-T11) at an interval of approximately two months in eight adult cats. In three cats, the spinal cord was transected at T12-T13. We collected electromyography (EMG) and kinematic data during quadrupedal and hindlimb-only locomotion before and after spinal lesions. We show that (1) cats spontaneously recover quadrupedal locomotion following staggered hemisections but require balance assistance after the second one, (2) coordination between the forelimbs and hindlimbs displays 2:1 patterns (two cycles of one forelimb within one hindlimb cycle) and becomes weaker and more variable after both hemisections, (3) left-right asymmetries in hindlimb stance and swing durations appear after the first hemisection and reverse after the second, and (4) support periods reorganize after staggered hemisections to favor support involving both forelimbs and diagonal limbs. Cats expressed hindlimb locomotion the day following spinal transection, indicating that lumbar sensorimotor circuits play a prominent role in hindlimb locomotor recovery after staggered hemisections. These results reflect a series of changes in spinal sensorimotor circuits that allow cats to maintain and recover some level of quadrupedal locomotor functionality with diminished motor commands from the brain and cervical cord, although the control of posture and interlimb coordination remains impaired.